Approach for developing coordinated rubrics to convey quality criteria in MCAD training. (June 2015) - Company, Pedro; Contero, Manuel; Otey, Jeffrey; Plumed, Raquel
Abstract: This paper describes an approach to convey quality-oriented strategies to CAD trainees by embedding quality criteria into rubrics so as to force CAD trainees to understand them early in their instruction. To this end, the paper analyzes how CAD quality criteria can be organized around quality dimensions and embedded into rubrics in order to enforce quality modeling during the CAD training of novice product designers. Hence, the ambit of this study is training with history-based parametric feature-based MCAD systems, although the general conclusions are believed to be adaptable to other CAD training scenarios. Furthermore, it introduces an approach based on progressive refinement, which results in an assertions map that indicates quality dimensions vs. sequence of tasks for CAD models. The map illustrates how the expand–contract strategy adapts the rubrics to CAD trainee progress and assists them in comprehending the different dimensions of the rubrics. The paper also highlights lessons learned on the suitability of using separate rubrics for different tasks, the need of accurately timing the expand–contract process, and on the convenience of supporting rubrics with suitable teaching, which must convey good practices and evaluation tools through rubrics. The experiments describe the different lessons learned and illustrate the suggested process for replicating our approach for further developing rubrics adapted to other scenarios. Highlights: Six main quality dimensions in CAD models for inexperienced CAD trainees. Approach to convey quality strategies to CAD trainees through rubrics. Assertions Map that adapts the rubrics to CAD trainee progress. Lessons learned on rubrics (separate, accurate timing, support with lecture notes).